Determinants of Malaysian salaried staff’s tax compliance intention in a self assessment system: The case of IRBM Bangi - Azwani, Mat Ghani @ Ab Ghani (2020)
This study attempted to investigate the determinants of Malaysian salaried staff’s tax compliance in a Self Assessment System. A theoretical framework was developed based on the Theory of Planned Behavior. The objectives of the study were to determine the level and relationship of attitude, subjective norms, and perceived behavioral control (tax knowledge and enforcement of penalty) towards tax compliance intention in a Self Assessment System among IRBM staff in its Bangi branch. Online questionnaires were used for data collection. Reliability analysis, factor analysis, descriptive analysis, and multiple regression analysis were conducted using the data collected from 159 respondents chosen via random sampling. The results of multiple regression analysis showed that independent variables that significantly influence the intention towards tax compliance are attitude, subjective norm, and tax knowledge. The findings also revealed that the independent variables tested explained 72.4% of the variance in tax compliance intention in Self Assessment System. Hence, the model used in this study was supported as suitable and was able to predict the dependent variable, tax compliance intention.